2018
DOI: 10.1111/ijfs.13816
|View full text |Cite
|
Sign up to set email alerts
|

Effects of gastrointestinal digestion models in vitro on phenolic compounds and antioxidant activity of juçara (Euterpe edulis)

Abstract: Summary This study evaluated the effects of different gastrointestinal digestion models in vitro on the bioaccessibility of phenolics and antioxidant activity in juçara frozen pulp. In the sequence, method 3 was applied to juçara fruit in three different stages of maturation (vitrin – reddish fruits, mature – purple fruits, tuíra – deep purple fruits). In the method applied, the final pH adopted was 5.0, in order to avoid interference in the assay used to determine the antioxidant activity, and BHT was used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…For the BV-NF extracts of African pumpkin, both the TPC and TFC were significantly ( p < 0.05) reduced after digestion, with a final bioaccessibility of 7% and 5% at the duodenal stage, respectively. Variance in bioaccessibility results with respect to the samples concerned (RV, BFV, and BV-NF) could be attributed to the differences in the presence of simple and highly polymerised metabolites [ 27 , 28 ]. Factors such as chemical structure modification, reduced or increased stability and association with other molecules (fibres, protein, and sugars) within the digesta may influence the bioaccessibility of phenolics [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For the BV-NF extracts of African pumpkin, both the TPC and TFC were significantly ( p < 0.05) reduced after digestion, with a final bioaccessibility of 7% and 5% at the duodenal stage, respectively. Variance in bioaccessibility results with respect to the samples concerned (RV, BFV, and BV-NF) could be attributed to the differences in the presence of simple and highly polymerised metabolites [ 27 , 28 ]. Factors such as chemical structure modification, reduced or increased stability and association with other molecules (fibres, protein, and sugars) within the digesta may influence the bioaccessibility of phenolics [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…For the ORAC hydroxyl donating activity, the raw African pumpkin showed significant ( p < 0.05) losses of 47% after complete digestion, while the spinach samples revealed significant ( p < 0.05) gains of 32%. Different ORAC activities between the African pumpkin and spinach could probably be due to the chemodiversity of the phenolic compounds of these vegetables, ranging from simple to highly polymerised molecules [ 28 ] which could be affected differently during digestion. Yang et al [ 40 ] reported no significant changes in ORAC activity for Basil after complete digestion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The in vitro gastrointestinal conditions lead to the hydrolysis of some phenolic compounds and interactions with the released products after hydrolysis. Other components of the food matrix released after gastric digestion can cause the change in molecular weight, in solubility, and in structure, which results in poor phenolic compounds extractability from the food matrix (Chen et al, 2016;Seraglio et al, 2018). The increase in the phenolic compounds content after the oral and gastric phase is noted especially for the clear variety.…”
Section: Discussionmentioning
confidence: 99%
“…The results also indicate that the phenolic compounds have a better antioxidant capacity and stronger function after simulated gastric digestion. Seraglio et al (2018) evaluated the effects of different gastrointestinal digestion models in vitro on the bioaccessibility of phenolics and antioxidant activity in juc ßara frozen pulp. It was found that the total phenolics and DPPH antioxidant activity of digestion group were much higher than the chemical extraction group (P < 0.05), indicating that when exposed to gastric and duodenal pH conditions, the ester bonds in phenolic compounds such as ellagitannins were hydrolysed to release mainly ellagic and gallic acid compounds with antioxidant activity.…”
Section: Discussionmentioning
confidence: 99%